Features of Education Giving to Children of Preschool Age (Journal of Pedagogical Inventions and Practices, 2022)
Education builds the spirit of teamwork and creates a sense of discipline in children, which helps in their growth as well as the growth and development of the nation in their future. Education acquired during childhood teaches and moulds a child in their communication and helps them to work as a team. High quality early childhood education gives children the best start in life. It provides important opportunities to learn and develop. Early childhood education can help your child make friends, develop independence and learn new routines. It also supports their transition to school.